Discovery of 15-deoxynaphthomycins activating the antioxidant NRF2-ARE pathway from Streptomyces sp. N50 via genome mining, global regulator introduction, and molecular networking - Kim, Min-Seon; Selvaraj, Baskar; Yeo Hee-Tae; Junsu Park; Lee, Jae Wook; Park, Jin-Soo (BioMed Central, 2025)
Genome mining is a promising avenue for expanding the repertoire of microbial natural products, which are important for drug development. This approach involves predicting genetically encoded small molecules by examining bacterial genomes via accumulated knowledge of microbial biosynthesis. However, it is also important that the microbes produce the predicted molecule in practice. Here, we introduce an endophytic Streptomyces sp. N50, which was isolated from the medicinal plant Selaginella tamariscina. Upon sequencing its entire genome, 33 biosynthetic gene clusters (BGCs) were identified in a chromosome and a megaplasmid. Subsequent genome mining revealed that the new 15-deoxynaphthomycin could be produced due to the presence of an enoyl reductase domain, which is absent in the known BGC of naphthomycin, a type of ansamycin antibiotics. In addition, the engineered strain with the introduction of the global regulatory gene afsR2 into N50 successfully produced 15-deoxynaphthomycins. Furthermore, molecular network analysis via MS/MS selectively confirmed the presence of additional sulfur-containing 15-deoxynaphthomycin congeners. Eventually, six new 15-deoxynaphthomycins were isolated and elucidated from the engineered strain N50. This family of compounds is known to exhibit various biological activities. Also, the presence of quinone moieties in these compounds, which are known to activate NRF2, they were tested for their ability to activate NRF2. Among the new compounds, three (1, 5, and 6) activated the antioxidant NRF2-ARE signaling pathway. Treatment with these compounds significantly elevated NRF2 levels in HepG2 cells and further induced the expression of NRF2 target genes associated with the antioxidant response. This study suggests that the combination of genome mining, gene engineering and molecular networking is helpful for generating new small molecules as pharmaceutical candidates from microorganisms.